Fornix Rupture in Duplex Kidney due to Internal Iliac Artery Aneurysm - Phitsanu Mahawong; Tanop Srisuwan; Kittipan Rerkasem (Case Reports in Urology)
A 70-year-old man presented with severe pain on the right side of the abdomen for 7 days. An abdominal CT angiographic scan showed an impending rupture of a large right internal iliac artery aneurysm which compressed to a right ureter causing hydroureteronephrosis. Fornix rupture of a right duplex kidney was also detected. Selective embolization of right gluteal arteries and then ligation of the right internal iliac artery and right ureterotomy with double J stenting were performed. At the 4-month follow-up appointment, an abdominal ultrasound demonstrated a decrease in the size of the aneurysm and no hydroureteronephrosis after the removal of double J stent.